Ionotropic glutamate receptor AMPA 1 is associated with ovulation rate. - Mayumi Sugimoto; Shinji Sasaki; Toshio Watanabe; Shota Nishimura; Atsushi Ideta; Maya Yamazaki; Keiko Matsuda; Michisuke Yuzaki; Kenji Sakimura; Yoshito Aoyagi; Yoshikazu Sugimoto (PLoS ONE, 2010)
Ionotropic glutamate receptors mediate most excitatory neurotransmission in the central nervous system by opening ion channels upon the binding of glutamate. Despite the essential roles of glutamate in the control of reproduction and anterior pituitary hormone secretion, there is a limited understanding of how glutamate receptors control ovulation. Here we reveal the function of the ionotropic glutamate receptor AMPA-1 (GRIA1) in ovulation. Based on a genome-wide association study in Bos taurus, we found that ovulation rate is influenced by a variation in the N-terminal leucine/isoleucine/valine-binding protein (LIVBP) domain of GRIA1, in which serine is replaced by asparagine. GRIA1(Asn) has a weaker affinity to glutamate than GRIA1(Ser), both in Xenopus oocytes and in the membrane fraction of bovine brain. This single amino acid substitution leads to the decreased release of gonadotropin-releasing hormone (GnRH) in immortalized hypothalamic GT1-7 cells. Cows with GRIA1(Asn) have a slower luteinizing hormone (LH) surge than cows with GRIA1(Ser). In addition, cows with GRIA1(Asn) possess fewer immature ovarian follicles before superovulation and have a lower response to hormone treatment than cows with GRIA1(Ser). Our work identified that GRIA1 is a critical mediator of ovulation and that GRIA1 might be a useful target for reproductive therapy.